Rancang Bangun Kompor Oli Bekas Sederhana dengan Blower Kompresor 2 Piston: Uji Coba Pembakaran 50 mL dalam 1 Menit - ferri festika; Misswar Abd; kamarullah; mustaqim; Riyan Satrizan; Arif Ramadhan (Jurnal Ilmiah Teknik Mesin, 2026)
AbstractThis study developed a simple waste oil stove equipped with a two piston compressor-based blower system without air pressure regulation. The oil was manually poured without an inlet pipe using a fixed volume of 50 mL. Compressed air was delivered through a flexible hose, partially blocked at the outlet with cloth to direct airflow toward the base of the combustion chamber. Observations showed that the initial flame was large and unstable, accompanied by sparks, but gradually diminished and transitioned into a stable blue flame as the fuel neared depletion. The entire 50 mL of oil was completely combusted within exactly 60 seconds with no liquid residue. This design offers a practical solution for rapid heating at micro scale applications, particularly in direct and economical utilization of waste-derived energy.